Malasakit Bilang Maskara ng Lupit: Mahabang Kamay ng COVID-19 - Baquiran Jr., Romulo P. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
When the series of COVID-19 lockdown began in Manila, the government touted a bayanihan approach to healing. Yet implementation by a largely police, military officials, and their assets proved ruinous, even fatal, for many Filipinos, even as those in power were craven in showing sympathy and selfish in taking advantage of the crisis for their own greedy motives.